(untitled) (The Review of Diabetic Studies, 2024)
Background: Acute Respiratory Distress Syndrome (ARDS) is a severe, life‑threatening form of acute lung injury characterized by diffuse alveolar damage, refractory hypoxemia, and high mortality among critically ill patients. Despite advances in supportive care and mechanical ventilation strategies, ARDS continues to represent a major challenge in critical care medicine due to its complex pathophysiology, diverse etiologies, and frequent association with multiorgan failure. Aim: This article aims to provide a comprehensive overview of ARDS with emphasis on its etiology, epidemiology, pathophysiology, clinical presentation, diagnostic evaluation, management strategies, complications, and long‑term outcomes, while highlighting patient safety and integrated care pathways in hospitalized patients. Methods: A narrative, integrative review approach was adopted. Current diagnostic frameworks, epidemiological data, and evidence‑based management practices were analyzed, with particular focus on the Berlin definition, lung‑protective ventilation strategies, adjunctive therapies, and multidisciplinary care principles. Results: ARDS remains prevalent among ICU patients, especially those with sepsis or severe pneumonia, with mortality strongly correlated to disease severity. Lung‑protective ventilation, prone positioning, conservative fluid management, and early identification of underlying causes significantly improve outcomes. However, survivors frequently experience prolonged functional, psychological, and rehabilitative challenges. Conclusion: ARDS requires early recognition, standardized diagnostic criteria, and an individualized, multidisciplinary treatment approach to reduce mortality and long‑term morbidity. Continued research into preventive and disease‑modifying strategies is essential.